2019
DOI: 10.31124/advance.9638417.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Resource Development and the Internet of Things

Abstract: <p>The Internet of Things (IoT) is affecting national innovation ecosystems and the approach of organizations to innovation and how they create and capture value in everyday business activities. The Internet of Things (IoT), is disruptive, and it will change the manner in which human resources are developed and managed, calling for a new and adaptive human resource development approach. The Classical Internet communication form is human-human. The prospect of IoT is that every object will have a unique w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The framework that examines the function of IoT in HR was finally built based on the results of the focused group's survey. The study on Internet of Things and human resource development that was suggested by (Yawson, Woldeab, and Osafo 2019). National centres of excellence are evolving due to the Internet of Things (IoT), as are how businesses approach development and generate value for stakeholders in their daily operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The framework that examines the function of IoT in HR was finally built based on the results of the focused group's survey. The study on Internet of Things and human resource development that was suggested by (Yawson, Woldeab, and Osafo 2019). National centres of excellence are evolving due to the Internet of Things (IoT), as are how businesses approach development and generate value for stakeholders in their daily operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study reviewed was by Yawson, Woldeab and Osafo (2018) which analysed the relationship between Human Resource Development and the Internet of Things. The author found that the Internet of Things (IoT) is disruptive, and it will change the manner in which human resources are developed and managed, calling for a new and adaptive human resource development approach.…”
Section: Internet Of Things and Resource Managementmentioning
confidence: 99%
“…The vista of the IoT as a pervasive array of devices bound to the Internet will fundamentally change DOI: 10.31124/advance.9638417.v1 how people think about what it means to be "online" (Rose et al, 2015). Technically, the IoT is not the result of a single novel technology; instead, several complementary technical developments and innovations provide systemic capabilities that help to bridge the gap between the virtual and physical world (Mattern & Floerkemeier, 2010).…”
Section: The Of Internet Of Thingsmentioning
confidence: 99%